2013
DOI: 10.7567/jjap.52.05fb01
|View full text |Cite
|
Sign up to set email alerts
|

A New Copper Alloy Film for Barrierless Si Metallization and Solder Bump Flip-Chip Application

Abstract: In this study, a copper alloy, Cu(MnN x ), film is developed by cosputtering Cu and Mn on a barrierless Si substrate within an Ar/N 2 gas atmosphere. The resulting alloy film exhibits good thermal stability and adhesion to the substrate with no noticeable interactions between the film and the substrate after annealing at 700 C for 1 h, indicating that the film is thermally stable. The alloy film shall be able to replace both the wetting and diffusion layers for the flip-chip solder joints in conventional under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…19) The degree of Cu oxidation is strongly related to the degree of outward diffusion of the additives. Previous studies [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] have shown that Cu(ReN) alloy films 25) are thermally stable up to 730 °C. Transition-metal nitrides have also received considerable attention owing to their desirable properties for many applications.…”
Section: Introductionmentioning
confidence: 99%
“…19) The degree of Cu oxidation is strongly related to the degree of outward diffusion of the additives. Previous studies [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] have shown that Cu(ReN) alloy films 25) are thermally stable up to 730 °C. Transition-metal nitrides have also received considerable attention owing to their desirable properties for many applications.…”
Section: Introductionmentioning
confidence: 99%
“…The new films created thus must imperatively retain high stability in existence under various high-temperature manufacturing environments where the films are to be processed and/or utilized. 7) In applying flip-chip technology® which uses bumps instead of gold wires to connect the chips® to popular electronic devices, such as cell phones, automotive parts, liquid crystal display (LCD)-driven IC products, high-level computer equipment, communication products, and the like that require a continuous reduction in area, height, and weight and/or withstanding harsh temperature, humidity, vibration, and even electromagnetic interference, and/or high-level performance, input-output (I/O) density, and cooling, and/or high I/O value and signal transmission quality, Cu, as traditionally chosen, must retain stability in existence under high temperatures and solderability to serve as a valid diffusion barrier and wetting layer 8) in controlled collapse chip connection, which often seems quite challenging to pure Cu. Some alloy films, 911) hence, have been developed for this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, other copper alloy films also appeared in the literature. [6][7][8][9] Barrierless metallization can simplify the manufacture of electronic devices and thereby reduce manufacturing costs. Alloyed Cu films, if prepared properly with insoluble components, e.g., Cu(TiIrN x ), 10) might form distinct microstructures offering good thermal properties, including thermal stability.…”
Section: Introductionmentioning
confidence: 99%